Implementasi Metode Rule-Based Scoring Pada Sistem Penilaian Resiko Penyakit Diabetes Dan Hipertensi Pada Pasien Umum Di Puskesmas Berbasis Web - Armando Tegar Hedonio; Sri Widoyoningrum (Fakultas Teknik Universitas Hamzanwadi, 2026)
Health screening procedures at primary healthcare facilities play a crucial role in early disease risk detection. However, the screening process at the Jelakombo Community Health Center is still performed manually, resulting in inadequate data recording and risk assessment. This study aims to design and implement a web-based disease risk assessment system for general patients using the Rule-Based Scoring method. The system was developed using the Laravel framework and a MySQL database, utilizing a digital questionnaire as a data collection medium. The Rule-Based Scoring method was used to calculate a total score based on user responses and classify risk levels into low, medium, and high categories. The results showed that the system was successfully implemented and all main functions of the system ran as required based on Black Box Testing. The system is capable of managing patient data, filling out questionnaires, automatically calculating risk scores, and displaying risk classification results digitally. The developed system can be used as an initial screening tool to support the early detection of disease risks in general patients at the Jelakombo Community Health Center.